Effects of an Unexpected and Expected Event on Older Adults’ Autonomic Arousal and Eye Fixations During Autonomous Driving - Stephenson, Alice C.; Eimontaite, Iveta; Caleb-Solly, Praminda; Morgan, Phillip L.; Khatun, Tabasum; Davis, Joseph; Alford, Chris (Frontiers in Psychology, 2020)
Driving cessation for some older adults can exacerbate physical, cognitive, and mental health challenges due to loss of independence and social isolation. Fully autonomous vehicles may offer an alternative transport solution, increasing social contact and encouraging independence. However, there are gaps in understanding the impact of older adults’ passive role on safe human-vehicle interaction, and on their well-being. 37 older adults (mean age ±SD=68.35 ±8.49 years) participated in an experiment where they experienced fully autonomous journeys consisting of a distinct stop (with a hazardous event versus without a hazardous event). The autonomous behavior of the vehicle was achieved using the Wizard of Oz approach. Subjective ratings of trust and reliability, and driver state monitoring including visual attention strategies (fixation duration and count) and physiological arousal (skin conductance and heart rate), were captured during the journeys. Results revealed that subjective trust and reliability ratings were high after journeys for both types of events. During a hazardous stop, overt visual attention was allocated towards the hazardous event, whereas during a safe stop, visual attention was directed towards the human-machine interface (HMI) and distributed across the central and peripheral driving environment. Elevated skin conductance level reflecting increased arousal persisted only after the hazardous event. The current study reveals possible visual attention limitations during a safety-critical event as demonstrated by increased sympathetic arousal and a smaller distribution of fixations towards the HMI and the periphery. These results suggest that safety-critical events occurring during passive fully automated driving may encourage deficit attentional strategies and elevate arousal mechanisms. To improve in-vehicle user experience for older adults, a driver state monitoring system could examine such psychophysiological indices to evaluate functional state and well-being. This information could then be used to make informed decisions on vehicle behavior and offer reassurance during elevated arousal linked to safety-critical events.